Áhrif heildstæðs stuðnings við jákvæða hegðun í frístund - Kolbrún Ingibjörg Jónsdóttir 1984- (2013)
The effects of implementing a School-Wide Positive Behavior Support (SWPBS) system in three elementary schools in Iceland were evaluated with a multiple baseline design across schools. Former studies on effects of SWPBS have used office discipline referral data and questionnaires. Here the effects were measured with direct observation of staff’s and students’ behavior. This study focuses on measures taken in the after-school program of each school. Data were collected twice yearly, one or two weeks each time, both before and after the implementation began. Results indicate that staff’s and students’ behavior improved. Staff’s positive attention, mild punishment, positive instructions, and supervision increased but staff’s inappropriate ignoring, inappropriate punishment and negative instructions decreased. Student’s problem behavior also decreased. Data collection is still ongoing.